2021
DOI: 10.1002/srin.202000549
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Nozzle Clogging through Fluid–Structure Interaction in the Continuous Steel Casting Process

Abstract: Analysis is performed for fluid–structure interaction (FSI) by nozzle clogging in the continuous steel casting process. The scope of the analysis is confined to a submerged entry nozzle (SEN) interacting with turbulent molten steel flow. The fluid and solid domains are discretized in a single framework of the finite volume method in the OpenFOAM‐Extend version. Flow displacement by the clog is tracked and modal analysis performed to predict the vibration frequencies due to clogging. Parametric study is perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
(29 reference statements)
0
7
0
Order By: Relevance
“…Some factors have been present since the original conception of the process, while others are much more recent, such as the injection of inert gases to reduce the blockage of the submerged entry nozzle (SEN) or the use of the electromagnetic brake. To date, understanding and quantifying how each of the equipment design aspects or operating conditions affects the quality of the steel produced in continuous slab casting machines remains a subject of research [1][2][3][4]. Despite this, there is broad agreement among specialists that the fluid flow pattern inside the mold called "double-roll" produces the least amount of defects in the product.…”
Section: Introductionmentioning
confidence: 99%
“…Some factors have been present since the original conception of the process, while others are much more recent, such as the injection of inert gases to reduce the blockage of the submerged entry nozzle (SEN) or the use of the electromagnetic brake. To date, understanding and quantifying how each of the equipment design aspects or operating conditions affects the quality of the steel produced in continuous slab casting machines remains a subject of research [1][2][3][4]. Despite this, there is broad agreement among specialists that the fluid flow pattern inside the mold called "double-roll" produces the least amount of defects in the product.…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al used the Arbitrary Lagrangian-Eulerian method to model the fluid-structure interaction and predict the vibration frequencies due to clogging. It was shown that the dominant frequency relecting the clogging process was primarily influenced by the total mass of clog and not much affected by the clogging locations in the SEN [107] .…”
Section: Prediction Of Nozzle Clogging By Numerical Simulationmentioning
confidence: 98%
“…There, collisions between the inclusions occur, which result in the agglomeration and clustering of alumina inclusions [13,22,25,28]. Among non-metallic inclusions, the deposition of alumina inclusions in tundish nozzles is believed to cause reduced molten steel pouring rate and nozzle blockage [10,13,22,25,26,29,30] while teeming the tundish from steel melts during castings. In addition to the submerged entry nuzzle and/or tundish nuzzle, such blockage may occur in the ladle shroud as well [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the submerged entry nuzzle and/or tundish nuzzle, such blockage may occur in the ladle shroud as well [31][32][33]. Therefore, there has been great interest in finding a practical and inexpensive technique to remove or reduce the amount of these inclusions prior to casting and/or while casting [30,31].…”
Section: Introductionmentioning
confidence: 99%